The use of laser therapy as a technological resource of nursing in the treatment of skin injuries (Research, Society and Development, 2022)
Introduction: Therapeutic laser has been a valuable resource in the treatment of injuries due to its healing capacity. This method is able to increase the proliferation of reparative cells in addition to collagen reorganization. It is worth noting that the nurse is a differentiated actor in the context of the treatment of skin lesions. Objective: this work seeks subsidies, within the existing literature, to ratify the hypothesis that the use of laser therapy as an optimizing resource for the healing process. Methods: Theoretical study of the integrative literature review type, carried out between April and July 2022, in the Virtual Health Library data source, using the descriptors Lasertherapy, Nursing Care and Healing, from the full text filters and available, documents type scientific articles; year of publication 2006 to 2022. After critical reading, a sample of 09 documents was established. Results and Discussion: The laser penetrates the skin and transfers the photons to the cells, to the electron chain of the mitochondrial membrane, increasing the rate of protons and ATP levels. Nurses exercise their autonomy in the face of different situations of the healing process, selecting the appropriate coverage, based on scientific evidence and their professional competence, which gives them the ability to develop their systematization of care. Conclusion: Research on this topic is of paramount importance for specialized care, since it uses laser extensively, which requires nurses to carry out the necessary training and specialize.